Investigation of Binary Solvents Performance for Regeneration of Iraqi 15W- 40 Waste Lubricant - Hussein, Hussein Qasim; Abdulkarim, Ali Laith (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The aim of this study was to investigate the effectiveness of binary solvent for regeneration of spent lubricating oil by extraction-flocculation process. The regeneration was investigated by bench scale experiments by using locally provided solvents (Heavy Naphtha, n-Butanol, and iso-Butanol). Solvents to used oil, mixing time, mixing speed and temperatures were studied as operating parameters. The performance on three estimated depended key parameters, namely the percentage of base oil recovered (Yield), percent of oil loss (POL), and the percent of sludge removal (PSR) were used to evaluate the efficiency of the employed binary solvent on extraction process. The best solvent to solvent ratio for binary system were 30:70 for Heavy Naphtha : n-Butanol (N:n-But) and Heavy Naphtha : iso-Butanol (N:iso-But). The optimum solvent to oil ratio or critical clarifying ratio (CCR) were 3.4, and 3.8 for N : n-But, and N : iso-But respectively. The optimized operating mixing time, mixing speed, and temperature which result in, maximum recovered base oil (87.75% and 88.88%), minimum oil losses (8.46% and 3.62%), and maximum sludge removal (5.63% and 6.12%), were (45 min, 700 rpm, 35 oC), and (30 min, 700 rpm, 35 oC ) for N:n-But, and N:Iso-But respectively.